Influence of SHGs on Empowerment of Rural Poor
Self Help Group (SHG) has emerged as a potential option/or empowerment of rural poor including women. The present study was conducted in randomly selected Kanker district of Chhattisgarh. A random sample of 12 SHGs, i.e. three from each of the four schemes viz. NABARD ’s SHG-Bank Linkage Programme (SBLP